Ultrasound irradiation activates purine metabolism and mitochondrial respiration via the MAPK signaling pathway in myotubes - Xiaoqi Ma; Noriaki Maeshige; Atomu Yamaguchi; Yunfei Fu; Jihao Xing; Qingcheng Guo; Hao Lin; Fuwen Lu; Hiroyo Kondo; Hidemi Fujino (Biochemistry and Biophysics Reports)
Background: Pulsed ultrasound (US) is widely used both as a diagnostic imaging tool and a therapeutic approach. However, many of the mechanisms underlying the therapeutic effects of non-thermal US remain unclear, especially in skeletal muscles, which play a crucial role in the body's metabolism. The aim of this study was to investigate the effects of US on myotubes. Methods: In this study, C2C12 myoblasts were utilized. After differentiating into myotubes, the cells were exposed to US irradiation at an intensity of 3.0 W/cm2, with a 20 % duty cycle, an acoustic frequency of 1 MHz, and a pulse repetition frequency of 100 Hz for 5 min. The cells were then collected and analyzed for genomic and metabolomic alterations, as well as mitochondrial function. Results: Cell viability remained unaffected after US irradiation. The mitogen-activated protein kinase (MAPK) signaling pathway was the most activated, while the expression of various RNAs was significantly altered. Purine metabolism was highly activated, with an increase in the abundance of metabolites associated with this pathway. Furthermore, mitochondrial respiration in the myotubes increased following US irradiation. Conclusion: This study investigated the impact of US irradiation on myotubes using genomic analysis, metabolomic analysis, and mitochondrial function. US irradiation activated the MAPK signaling pathway, which in turn enhanced purine metabolism and improved mitochondrial respiration.